Religious Moderation in Pesantren Culture Era Post-Truth for Santri-College Students of Unwahas and UIN Walisongo - Ali Imron; Fatah Syukur (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
This study aims to find out: 1) understanding and moderation of the religious attitudes of Islamic boarding school students in Unwahas and Walisongo, and 2) Islamic boarding school culture in the post-truth era at student boarding schools in Unwahas and Walisongo. The type of this research is a qualitative field research. The technique of collecting data using observation, documentation, interviews and FGD methods. The results of this study are: 1) understanding and moderation of the religious attitudes of students at UIN Walisongo and Unwahas Semarang manifested in several ways, including: national commitment, tolerance, anti-violence and radicalism and respect for local wisdom inspired by the norm of muhafadzatu 'ala al-qadim al-shalih wa al-akhdzu bi al-jadid al-ashlah. 2) Pesantren culture in the post-truth era experienced an interesting dynamic process. The development of digital media has made pesantren have a new tradition by broadcasting the recitation of the kitab kuning, dhikr, and reading dziba' live - virtual. Although the pesantren culture has spread in virtual areas, offline pesantren activities with the community are still ongoing.